Perspectivas de gestação e parto de três gerações de mulheres quilombolas : compreensões a partir da abordagem centrada na pessoa - Costa, Larissa Léia da (2023)
The gestational and parturition processes are permeated by care practices, subjective questions and biopsychosocial changes. Thus, considering three generations of women from the Bocaina quilombo, in Mato Grosso, this study aimed to identify and understand the possible transitions of practices in the assistance during pregnancy and childbirth, considering the implementation and execution of Labor Humanization Policies, as well as which senses and meanings had been experienced about gestating and giving birth, in order to understand the possible impacts among these generations. For this, four individual psychological-phenomenological interviews were carried out, having as trigger: “how was the gestational and parturition process for you?” The qualitative and experiential research was done under the premises of the Person-Centered Approach (PCA), a theoretical basis that has as fundamental concepts: the updating trend, the congruence, the unconditional positive consideration and the empathic understanding. To get to these women, the snowball technique was used. Regarding the understanding of information, it was organized in units of meanings and considered from the PCA premises, in parallel with significant positions of women authors on black feminism. Thus, this study, with the simple and symbolic view of four participants, obtained indicators demonstrating that the older generations went through these experiences helped by midwives who, in those times, offered guidelines, care and security. It showed, in the same way, that they experienced gestation and giving birth, as was possible, appearing to have been kept in their memories as something understood and situated in the past, where they felt nurtured. It should be highlighted that one participant of the second-generation group fully experienced both periods. She seemed to feel out of place at the second time, but understood the effectiveness of services in contemporary times. In the case of the younger participants, who emerged and were brought up in totally distinct environments from their ancestral counterparts, were assisted from the beginning by the modern health policies both in the public and private network, and went through these processes experiencing loneliness, negligence and social constraints. These women expressed themselves more emotionally in relation to the experience which appeared very present and distressing in their memories. The event that happened in conditions that are understandably vulnerable but, in certain situations collaborative, left behind pain and anguish. For these women, the alternative is to (re)exist.